Exploring Shinto - Pye, Michael 1939- (Equinox Publishing Ltd, 2020)
On writing the history of "Shinto" / Mark Teeuwen -- Shinto spaces and shinbutsu interaction in the Noh / Dunja Jelesijevec -- Introducing the faith of Shinshūkyō / Masanori Yoshimura
Literaturangaben
Keywords: Geschichte; Shintō; Shinto; Aufsatzsammlung